HUBUNGAN MOTIVASI PERAWAT DENGAN KEPATUHAN PELAKSANAAN PEMBERIAN OBAT ORAL - Nila ' Putriana; Sofiana ' Nurchayati; Sri Utami ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The motivation of nurses is influenced by internal and external factors that affect the implementation of the oral medication obeyed in Utama Room of Arifin Achmad Public Hospital Pekanbaru. Job Motivation is a boost of encouragement from the nurse consist of (a sense of awareness, sense of responsibility, work interests, loyalty, discipline) and encouragement from the outside (the recognition of others, opportunities for advancement, promotion and career opportunities, a sense of security in the work, remuneration appropriate and lack of monitoring of others) that directs the actions and behavior of nurses to achieve its objectives. The purpose of this research was to determine the relationship of work motivation nurse with oral medication obeyed. Design research was descriptive correlation with cross sectional approach. The total sample of 46 respondents using purposive sampling technique. Measuring tools such as questionnaires and observation sheets. Results of univariate analysis obtained entirely of women (100%) mostly educated D3 with employment status largely honorary workers (76.1%), long work over 4 years (43.5%). While the bivariate analysis results obtained ρ value 0.004 < (α = 0.05) using the chi square test, the conclusion there is a significant relationship between motivation nurse with compliance implementation oral medication obeyed. Suggested for hospital nurses supervise compliance and further increase the motivation of nurses and provide reword and punishment to those who do not run the SOP. Keywords: obedience, motivation nurse, oral medication obeyed Bibliography: 49 (2003-2014)